Small changes in thermal conditions hinder marathon running performance in the tropics. Issue 4 (2nd October 2022) - Tan, Glenn C. W.; Zheng, Kaiyuan; Cheong, Wee K.; Byrne, Christopher; Iversen, Jan N.; Lee, Jason K. W.
ABSTRACT: We examined marathon performance of the same group of runners in relation to small changes in dry bulb temperature (Tdb ) and wet bulb temperature (Twb ) across 3 consecutive y, and investigated whether performance was poorer during an evening marathon compared with morning marathons. Marathon results were obtained from the 2017, 2018, and 2019 Standard Chartered Singapore Marathons. Tdb, Twb, Td, relative humidity, and absolute humidity were gathered for each marathon. K-means clustering and linear regressions were performed on 610 runners who participated in all three marathons. Analysis of the 610 runners' marathon performance was contrasted with Tdb and Twb . Linear regressions were also performed on 190 runners filtered by percentile, yielding similar results. For clusters with similar Tdb from all runners K-means clustering, an increase in mean Twb by 1.5°C coincided with an increase in finishing time by 559 s (9.3 min) (p < 0.033). Twb hinders marathon performance more than Tdb, with each percentage rise in Tdb and Twb resulting in an increase in net time by 7.6% and 39.1%, respectively (p < 0.025). Male and female runners' response to Tdb and Twb changes were similar (overlap in 95% confidence intervals for the respective regression coefficients). In conclusion, small variations in environmental parameters affected marathon performance, with Twb impairing marathon performance more than Tdb . Marathon performance was likely better in the morning than evening, possibly due to time of day differences, along with unfavorable Tdb that superseded training effects and the effects of lower Twb .